Comparison of ejector predicted performance by thermodynamic and CFD models. (August 2016) - Croquer, Sergio; Poncet, Sébastien; Galanis, Nicolas
Highlights: Comparisons between thermodynamic and CFD models for supersonic ejectors. The ejector performance with perfect gas is governed by non-dimensional quantities. The position of the shock varies linearly with the compression ratio. A good agreement has been obtained in terms of isentropic and mixing efficiencies. Abstract: This paper presents a systematic comparison of ejector performance predictions by a thermodynamic and a CFD model for different operating conditions. The dimensions of the ejector were determined by the thermodynamic model and used in the CFD model. The thermodynamic model predicts higher entrainment ratios for double choking operation and somewhat different values of the critical and limiting pressure ratios. The CFD model validates the similarity solutions characteristic of ejectors using perfect gases. It also shows that the position of the shock varies linearly with the compression ratio in qualitative agreement with the assumption used in the thermodynamic model. Finally, the isentropic and mixing efficiencies obtained by the two approaches are favorably compared.